Kebijakan Pendidikan dalam Konteks Meningkatkan Pembelajaran melalui Guru Penggerak - Silvia Nurwanci; Gantina Gantina; Riyadi Rafiki; Leli Halimah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Education policy aims to enhance the quality of student-centered learning through various innovations and interventions, one of which is the Teacher Leadership Program (Program Guru Penggerak). This government-initiated program is designed to empower teachers as innovative and inspirational leaders in both schools and the broader educational community. The program encourages teachers to take active roles as agents of change, emphasizing learning that facilitates the development of students' character, competencies, and creativity. This study employs a literature review method to examine the issue by elaborating on various sources, such as journals, books, and other relevant literature. Through the analysis and synthesis of information from these sources, the study seeks to deepen understanding of the topic under review. By adopting project-based approaches, collaboration, and reflective teaching practices, the Teacher Leadership Program aims to develop teachers' pedagogical skills, leadership capabilities, and communication competencies to support active learning. The implementation of this policy faces various challenges, including mindset shifts, curriculum adjustments, and the improvement of educational infrastructure. Nevertheless, with consistent policy support and stakeholder collaboration, the Teacher Leadership Program is believed to enhance the quality of education, strengthen the learning ecosystem, and produce adaptive, creative, and highly competitive future generations.